Communication and soft power: Exploring the role of international media in building national image - Almakaty, Safran Safar (Edelweiss Applied Science and Technology, 2025)
This paper investigates the complex relationship between international media and the soft power wielded by nations, focusing on how various communication strategies contribute to shaping national identities and images. Utilizing qualitative research methodology, this study is grounded in Joseph Nye’s influential concept of soft power, which suggests that nations are increasingly prioritizing cultural appeal and effective communication over coercive measures to enhance their influence on the global stage. The research findings are structured into three main sections: the historical evolution of communication strategies in the international arena; the significant impact of media representations on the public perception of nations; and the contemporary challenges and opportunities brought about by digital platforms. Each section emphasizes the dual capacity of the media to mold perceptions, illustrating how favorable narratives can bolster a nation’s soft power, whereas negative portrayals can erode it. In conclusion, this paper asserts that adept media strategies are essential for countries to navigate the intricate landscape of international relations and foster positive global perceptions. It also encourages further research to deepen the understanding of these critical dynamics.